1995
DOI: 10.1002/marc.1995.030160709
|View full text |Cite
|
Sign up to set email alerts
|

Substituent effect in anionic polymerization of β‐lactones initiated by alkali metal alkoxides

Abstract: The influence of methyl substituent on the mechanism of the ring-opening polymerization of p-lactones initiated by alkali metal alkoxides is discussed. Attention has been paid to the effect of the substituent position in the monomer molecule on the ring-opening mechanism, the 3,3-dimethyl-2-oxetanone (pivalolactone), 4-methyl-2-oxetanone @-butyrolactone) and 2-oxetanone @-propiolactone) being chosen as model monomers. Moreover, it was found unexpectedly that in the case of pivalolactone polymerization, besides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…The mechanisms of ROP of lactone and lactide by various initiators have been concerned by researchers for a long time. It has been revealed that ring‐opening polymerization of some lactone such as β‐butyrolactone and its derivatives initiated by strong base such as alkali‐metal alkoxide either through acyl‐oxygen bond cleavage or by alkyl‐oxygen bond split 71–73. Recently, Soum and coworkers59 demonstrated that the ring‐opening polymerization of ε‐caprolactone, δ‐valerolactone, and D , L ‐lactide took place through acyl‐oxygen bond cleavage resulting in the polymer chains capped with lanthanum alkoxide groups.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms of ROP of lactone and lactide by various initiators have been concerned by researchers for a long time. It has been revealed that ring‐opening polymerization of some lactone such as β‐butyrolactone and its derivatives initiated by strong base such as alkali‐metal alkoxide either through acyl‐oxygen bond cleavage or by alkyl‐oxygen bond split 71–73. Recently, Soum and coworkers59 demonstrated that the ring‐opening polymerization of ε‐caprolactone, δ‐valerolactone, and D , L ‐lactide took place through acyl‐oxygen bond cleavage resulting in the polymer chains capped with lanthanum alkoxide groups.…”
Section: Resultsmentioning
confidence: 99%
“…40 The second route of producing PLA is to collect, purify, and ring-open and polymerize lactide to yield high molecular weight (average M w > 100 000) PLA. 40,43,44 The combination of the chiral lactic acid monomers (Fig. 2) or the depolymerization of low molecular weight PLA ( Fig.…”
Section: Poly(lactic Acid) Plasticsmentioning
confidence: 99%
“…The degradation rate of PLA mainly depends on the temperature during hydrolysis, the size, the shape and the isomer ratio of the PLA [13]. Landfill has been recognized as a cheapest and economic way to bury wastes under the soil.…”
Section: Introductionmentioning
confidence: 99%